2006
DOI: 10.1016/j.cell.2006.05.035
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 Controls Phagosomal pH to Regulate Antigen Processing during Crosspresentation by Dendritic Cells

Abstract: To initiate adaptative cytotoxic immune responses, proteolytic peptides derived from phagocytosed antigens are presented by dendritic cells (DCs) to CD8+ T lymphocytes through a process called antigen "crosspresentation." The partial degradation of antigens mediated by lysosomal proteases in an acidic environment must be tightly controlled to prevent destruction of potential peptides for T cell recognition. We now describe a specialization of the phagocytic pathway of DCs that allows a fine control of antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

58
814
3
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 758 publications
(881 citation statements)
references
References 42 publications
58
814
3
6
Order By: Relevance
“…These mechanisms could correspond to those observed by us in the absence of DC stimulation with PMA. Savina et al [50] suggest that in murine DC, NADPH oxidase is mainly involved in antigen processing. Our results indicate that NADPH oxidase also plays a role in Candida-killing activity of DC, in particular when ROS production is enhanced by IFN.…”
mentioning
confidence: 99%
“…These mechanisms could correspond to those observed by us in the absence of DC stimulation with PMA. Savina et al [50] suggest that in murine DC, NADPH oxidase is mainly involved in antigen processing. Our results indicate that NADPH oxidase also plays a role in Candida-killing activity of DC, in particular when ROS production is enhanced by IFN.…”
mentioning
confidence: 99%
“…Nevertheless, inhibition of Ag degradation is often related to increased Ag presentation, as demonstrated using Takahashi et al, 1989 protease inhibitors ( ), antigen resistant to degradation ( ) or modulation of intravacuolar pH ( Vidard et al, 1991Delamarre et al, 2006 ). Indeed, reduced intracellular proteolysis avoids the destruction of T cell epitopes, favoring the production of Savina et al, 2006 peptide-MHC classs II complexes. This is particularly important in cells such as macrophages which possess elevated degradation capacity due to their high protease content.…”
Section: Inhibitory Effect Of C3 Upon Tt Proteolysis In U937mentioning
confidence: 99%
“…Several studies consistently showed that the phagosomal pH of macrophages decreases rapidly and equilibrates around pH 5.0 in 30 min (Nyberg et al, 1989;Lukacs et al, 1990Lukacs et al, , 1991Sturgill-Koszycki et al, 1994;Rybicka et al, 2010). To add to the variability, a phagosomal alkalization was reported in dendritic cells, the phagosomal pH reaching pH 7.6 within 1 hour of phagocytosis in these phagocytes (Savina et al, 2006). Limited levels of proteolysis within the phago-lysosomal system are critical for efficient antigen presentation by dendritic cells, and the alkalinization was proposed to prevent excessive proteolysis and antigen degradation.…”
mentioning
confidence: 95%
“…The alkalinization was strictly dependent on the activity of NOX2, and NOX2-deficient cells that did not produce superoxide failed to alkalinize (Savina et al, 2006;Mantegazza et al, 2008). Because the phagosomal alkalinization was linked to the ROS production, the alkalinization of dendritic cells phagosomes was attributed to the consumption of protons within phagosomes during the conversion of superoxide anions into hydrogen peroxide (Savina et al, 2006). However, as discussed above, superoxide production by NOX2 requires the movement of counter-ions to compensate for the charge of the electrons.…”
mentioning
confidence: 99%
See 1 more Smart Citation